The Role of Competitive Advantage, Marketing Innovation and Product Innovation on Marketing Performance - Indra Laksana; Audita Nuvriasari (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the role of competitive advantage, marketing inovation and product inovation on the marketing performance of coffee shop in Yogyakarta. The population in this study is coffee shop business actors who have been running their business for at least the last 3 years. The sampling technique used was purposive sampling with a sample 100 coffee shops in Yogygakarta. The results of this research analyze show that: (1) Competitive advantage has a potitive and significant effect on marketing performance, (2) Marketing innovation has a positive and significant effect on marketing performance, (3) Product inovation has a positive and significant effect on marketing performance.